Evaluation of Image Quality of a 32-Channel versus a 12-Channel Head Coil at 1.5T for MR Imaging of the Brain - Parikh, P.T.; Sandhu, G.S.; Blackham, K.A.; Coffey, M.D.; Hsu, D.; Liu, K.; Jesberger, J.; Griswold, M.; Sunshine, J.L. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Multichannel phased-array head coils are undergoing exponential escalation of coil element numbers. While previous technical studies have found gains in SNR and spatial resolution with the addition of element coils, it remains to be determined how these gains affect clinical reading. The purpose of this clinical study was to determine if the SNR and spatial resolution characteristics of a 32-channel head coil result in improvements in perceived image quality and lesion evaluation. MATERIALS AND METHODS: Twenty-one patients underwent MR imaging of the brain at 1.5T sequentially with both a 12-channel and a 32-channel receive-only phased-array head coil. Axial T2WIs, T1WIs, FLAIR images, and DWIs were acquired. Anonymized images were compared side-by-side and by sequence for image quality, lesion evaluation, and artifacts by 3 neuroradiologists. Results of the comparison were analyzed for the preference for a specific head coil. RESULTS: FLAIR and DWI images acquired with the 32-channel coil showed significant improvement in image quality in several parameters. T2WIs also improved significantly with acquisition by the 32-channel coil, while T1WIs improved in a limited number of parameters. While lesion evaluation also improved with acquisition of images by the 32-channel coil, there was no apparent improvement in diagnostic quality. There was no difference in artifacts between the 2 coils. CONCLUSIONS: Improvements in SNR and spatial resolution attributed to image acquisition with a 32-channel head coil are paralleled by perceived improvements in image quality. BG/ICbasal ganglia/internal capsuleChchannelCNcranial nerveCNScentral nervous systemCPcircularly polarizedCScentrum semiovaleDWIdiffusion-weighted imagingFLAIRfluid-attenuated inversion recoveryGWgray-whiteLVlateral ventricleMB/RNmidbrain/red nucleusMCPmiddle cerebellar peduncleMRAMR angiographyN/Anot applicableNMRnuclear magnetic resonancePIparallel imagingSNRsignal-to-noise ratioSTsection thicknessTEMtransverse electromagneticT1WIT1-weighted imageT2WIT2-weighted imageWMTwhite matter tracts